2022
DOI: 10.1039/d2cc02773a
|View full text |Cite
|
Sign up to set email alerts
|

Integration of H2V3O8 nanowires and a GaN thin film for self-powered UV photodetectors

Abstract: A self-powered ultraviolet (UV) photodetector was successfully constructed through combining H2V3O8 nanowires (NWs) and a GaN thin film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Zhang and Song [142] reported that by solution depositing a highly p-type CuZnS layer on GaN, a fast response speed of 0.14/40 ms and an ultrahigh photo/dark current ratio reaching 3 × 10 8 were obtained under 350 nm light illumination at zero bias. Dou et al [143] reported that by integrating the H 2 V 3 O 8 nanowires onto the GaN film via the dipcoating method, an n-n heterojunction self-powered UV-PD was realized. Furthermore, n-SnO 2 microwires were deposited on a p-GaN epitaxial layer, and a monolithically integrated UV light-emitting-diode (LED) with a PD was obtained [144].…”
Section: P-n Heterojunctions With Other Materials Systemsmentioning
confidence: 99%
“…Zhang and Song [142] reported that by solution depositing a highly p-type CuZnS layer on GaN, a fast response speed of 0.14/40 ms and an ultrahigh photo/dark current ratio reaching 3 × 10 8 were obtained under 350 nm light illumination at zero bias. Dou et al [143] reported that by integrating the H 2 V 3 O 8 nanowires onto the GaN film via the dipcoating method, an n-n heterojunction self-powered UV-PD was realized. Furthermore, n-SnO 2 microwires were deposited on a p-GaN epitaxial layer, and a monolithically integrated UV light-emitting-diode (LED) with a PD was obtained [144].…”
Section: P-n Heterojunctions With Other Materials Systemsmentioning
confidence: 99%